Resin composition

JP7652196B2Active Publication Date: 2025-03-27AJINOMOTO CO INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023002690
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-01-11
Publication Date
2025-03-27
Estimated Expiration
2043-01-11

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、ガラス転移温度が高く、誘電率が低い硬化物を得ることが可能な溶融粘度が低い樹脂組成物;当該樹脂組成物を用いたプリプレグ;プリント配線板;半導体チップパッケージ;及び半導体装置を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652196000011
    Figure 0007652196000011
  • Figure 0007652196000001
    Figure 0007652196000001
  • Figure 0007652196000002
    Figure 0007652196000002
Patent Text Reader

Abstract

To provide a resin composition or the like with low melt viscosity, capable of producing a cured product with a high glass transition temperature and a low dielectric constant.SOLUTION: A resin composition contains (A) liquid epoxy resin, (B) a solid epoxy resin with an epoxy equivalent of 200 g / eq. or more, (C) a maleimide compound, and (D) a cresol novolac phenolic resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. The present invention further relates to a prepreg, a printed wiring board, a semiconductor chip package, and a semiconductor device obtained by using the resin composition. [Background technology]

[0002] A known insulating material that can be used as an insulating layer for a semiconductor chip package is, for example, a prepreg in which a base material such as a glass cloth is impregnated with a resin composition (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-185221 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there has been a demand for larger semiconductor chip packages in order to achieve higher functionality. When the semiconductor chip package is enlarged, the stress on the insulating layer made of the cured resin composition increases, which may cause the semiconductor chip package to warp. In addition, as the semiconductor chip package becomes larger, there is a demand for a higher glass transition temperature (Tg) to improve the mechanical strength of the insulating layer.

[0005] A method of using a liquid epoxy resin to suppress the occurrence of warping and further using a maleimide compound to obtain a cured product with a high glass transition temperature can be considered, but this sometimes results in a high dielectric constant of the cured product.

[0006] Thus, there is a demand for a resin composition that has a low melt viscosity in order to suppress the occurrence of warping, and that can give a cured product with a high glass transition temperature and a low dielectric constant.

[0007] The present invention has been devised in view of the above problems, and has an object to provide a resin composition having a low melt viscosity and capable of giving a cured product having a high glass transition temperature and a low dielectric constant; a prepreg using the resin composition; a semiconductor chip package; and a semiconductor device. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above-mentioned problems, the present inventors have found that by using a resin composition containing a combination of (A) a liquid epoxy resin, (B) a solid epoxy resin having an epoxy equivalent of 200 g / eq. or more, (C) a maleimide compound, and (D) a cresol novolac phenolic resin as an insulating material, it is possible to obtain a cured product having a low melt viscosity, a high glass transition temperature, and a low dielectric constant, and have thus completed the present invention.

[0009] That is, the present invention includes the following. [1] (A) Liquid epoxy resin, (B) a solid epoxy resin having an epoxy equivalent of 200 g / eq. or more; (C) a maleimide compound, and (D) A resin composition containing a cresol novolac type phenolic resin. [2] The resin composition according to [1], wherein component (A) contains a difunctional or higher functional liquid epoxy resin. [3] The resin composition according to [1] or [2], wherein the component (B) contains a trifunctional solid epoxy resin. [4] The resin composition according to any one of [1] to [3], wherein the component (B) contains a resin represented by the following formula (B-1): [ka] In formula (B-1), R 1 , R 2 , and R 3 each independently represents an alkylene group which may have a substituent, an oxygen atom, or an oxyalkylene group which may have a substituent; R 4represents an alkyl group which may have a substituent, or a hydrogen atom; R 5 represents an alkylene group which may have a substituent. [5] The resin composition according to any one of [1] to [4], wherein the content of the component (A) is 2% by mass or more and 12% by mass or less, when the total amount of the components (A) to (D) is taken as 100% by mass. [6] The resin composition according to any one of [1] to [5], wherein the content of the (B) component is 15% by mass or more and 55% by mass or less, when the total amount of the (A) to (D) components is taken as 100% by mass. [7] The resin composition according to any one of [1] to [6], wherein the content of the (C) component is 3% by mass or more and 20% by mass or less, when the total amount of the (A) to (D) components is taken as 100% by mass. [8] The resin composition according to any one of [1] to [7], wherein the content of the (D) component is 15% by mass or more and 50% by mass or less, when the total amount of the (A) to (D) components is taken as 100% by mass. [9] The resin composition according to any one of [1] to [8], wherein the content of the (D) component is greater than the content of the (C) component.

[10] The resin composition according to any one of [1] to [9], further comprising (E) an inorganic filler.

[11] The resin composition according to

[10] , wherein the content of the (E) component is 40% by mass or more and 80% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass.

[12] The resin composition according to any one of [1] to

[11] , further comprising (F) a curing accelerator.

[13] The resin composition according to

[12] , wherein the component (F) contains an imidazole-based curing accelerator.

[14] The resin composition according to any one of [1] to

[13] , wherein the resin composition contains 0.5 mass % or more and 3 mass % or less of a solvent, relative to 100 mass % of all components of the resin composition.

[15] A prepreg comprising a sheet-like fiber substrate and the resin composition according to any one of [1] to

[14] impregnated into the sheet-like fiber substrate.

[16] A circuit board comprising a cured layer formed from a cured product of the resin composition according to any one of [1] to

[14] .

[17] A semiconductor chip package comprising the circuit board according to

[16] and a semiconductor chip mounted on the circuit board.

[18] A semiconductor device comprising the semiconductor chip package according to

[17] . Effect of the Invention

[0010] According to the present invention, it is possible to provide a resin composition having a low melt viscosity and capable of giving a cured product having a high glass transition temperature and a low dielectric constant; a prepreg using the resin composition; a printed wiring board; a semiconductor chip package; and a semiconductor device. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic side view showing an example of two test tubes used to determine whether an epoxy resin is in a liquid state, a semi-solid state, or a solid state. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0013] The determination of whether liquid, solid, or semi-solid epoxy resin is liquid, solid, or semi-solid is made in accordance with the "Method of Confirming Liquid State" in Appendix 2 of the Ministerial Ordinance on the Testing and Properties of Hazardous Materials (Ministry of Home Affairs Ordinance No. 1 of 1989). The specific determination method is as follows:

[0014] (1) Equipment Thermostatic water bath: Use a container equipped with an agitator, heater, thermometer, and automatic temperature controller (capable of controlling temperature to within ±0.1°C) and with a depth of 150 mm or more. In assessing the epoxy resins used in the examples described below, a combination of a low-temperature constant temperature water bath (model BU300) and an input type thermostat Thermomate (model BF500), all manufactured by Yamato Scientific Co., Ltd., was used. Approximately 22 liters of tap water was placed into the low-temperature constant temperature water bath (model BU300), the Thermomate (model BF500) attached to it was turned on and set to the set temperature (20°C or 60°C), and the water temperature was fine-tuned with the Thermomate (model BF500) to within ±0.1°C of the set temperature; however, any device capable of similar adjustments can be used.

[0015] Test tube: The test tubes used are cylindrical, flat-bottomed transparent glass tubes with an inner diameter of 30 mm and a height of 120 mm, as shown in Fig. 1, with marked lines 11A and 12B at heights of 55 mm and 85 mm from the bottom of the tube, respectively, and a test tube 10a for liquid determination, with the mouth of the test tube sealed with a rubber stopper 13a, and a test tube 10b for temperature measurement, with the mouth of the test tube sealed with a rubber stopper 13b of the same size and marked lines with a hole in the center for inserting and supporting a thermometer, and a thermometer 14 inserted into the rubber stopper 13b. Hereinafter, the marked line at a height of 55 mm from the bottom of the tube will be referred to as "line A", and the marked line at a height of 85 mm from the bottom of the tube will be referred to as "line B".

[0016] As the thermometer 14, a thermometer for measuring the freezing point (SOP-58 scale range 0 to 100°C) as specified in JIS B7410 (1982) "Glass thermometer for testing petroleum products" is used, but any thermometer that can measure temperatures in the range of 0 to 100°C will do.

[0017] (2) Test procedure The sample that has been left for 24 hours or more under atmospheric pressure at a temperature of 60±5°C is poured into the liquid determination test tube 10a shown in Figure 1(a) and the temperature measurement test tube 10b shown in Figure 1(b) up to the 11A line. The two test tubes 10a and 10b are placed upright in a low-temperature constant temperature water bath so that the 12B line is below the water surface. The thermometer is placed so that its bottom end is 30 mm below the 11A line.

[0018] After the sample temperature reaches the set temperature ±0.1° C., maintain the state for 10 minutes. After 10 minutes, remove the liquid state determination test tube 10a from the low-temperature constant temperature water bath and immediately lay it horizontally on a horizontal test table. Use a stopwatch to measure and record the time it takes for the tip of the liquid level in the test tube to move from line 11A to line 12B.

[0019] Similarly, for samples that have been left for 24 hours or more under atmospheric pressure at a temperature of 20±5°C, the test is carried out in the same manner as for samples that have been left for 24 hours or more under atmospheric pressure at a temperature of 60±5°C, and the time it takes for the tip of the liquid level in the test tube to move from line 11A to line 12B is measured and recorded with a stopwatch.

[0020] At 20°C, epoxy resins that have a measured time of 90 seconds or less are judged to be liquid. A resin that has a measured time of more than 90 seconds at 20°C and less than 90 seconds at 60°C is judged to be a semi-solid epoxy resin. At 60°C, epoxy resins that last for more than 90 seconds are considered to be solid.

[0021] In the following description, the term "dielectric constant" refers to the "relative dielectric constant" unless otherwise specified.

[0022] [Resin composition] The resin composition of the present invention contains (A) a liquid epoxy resin, (B) a solid epoxy resin having an epoxy equivalent of 200 g / eq. or more, (C) a maleimide compound, and (D) a cresol novolac phenolic resin. By using such a resin composition, it is possible to obtain a cured product that is suppressed from warping and has a high glass transition temperature and a low dielectric constant. In addition, it is usually possible to obtain a cured product that has a low linear thermal expansion coefficient.

[0023] The resin composition may further contain optional components such as (E) an inorganic filler, (F) a curing accelerator, (G) a semi-solid epoxy resin, (H) a solid epoxy resin having an epoxy equivalent of less than 200 g / eq., (I) an organic filler, (J) other additives, and (K) a solvent, as necessary. Each component contained in the resin composition will be described in detail below.

[0024] <(A) Liquid epoxy resin> The resin composition contains a liquid epoxy resin (A) as the component (A). By including the component (A) in the resin composition, it is possible to reduce the melt viscosity, and as a result, it is possible to suppress the occurrence of warping of the cured product. The component (A) may be used alone or in combination of two or more types.

[0025] From the viewpoint of obtaining the effect of the present invention remarkably, the liquid epoxy resin (A) preferably contains a liquid epoxy resin having two or more epoxy groups in one molecule and having two or more functionalities. The liquid epoxy resin (A) preferably has an aromatic structure, and when two or more kinds of liquid epoxy resins (A) are used, it is more preferable that at least one of them has an aromatic structure. The aromatic structure is a chemical structure generally defined as aromatic, and includes polycyclic aromatic rings and aromatic heterocycles. The ratio of the liquid epoxy resin (A) having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more, based on 100% by mass of the non-volatile components of the liquid epoxy resin (A).

[0026] As the (A) liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, glycidyl amine type epoxy resin, and epoxy resin having a butadiene structure are preferred, and bisphenol A type epoxy resin and bisphenol F type epoxy resin are more preferred.

[0027] Specific examples of liquid epoxy resins include Mitsubishi Chemical's "828US", "jER828EL" (bisphenol A type epoxy resin), "jER807" (bisphenol F type epoxy resin), and "jER152" (phenol novolac type epoxy resin); Mitsubishi Chemical's "630" and "630LSD" (glycidylamine type epoxy resin); and ADEKA's "ED-523T" (glycirol type epoxy resin (ADEKA glycirol)), "EP-3980S" (glycidylamine type epoxy resin), and "EP-4088S" (dicyclopentadiene type epoxy resin). resin); "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase Chemtex Corporation; "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) and "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane) manufactured by Nippon Steel Chemical & Material Co., Ltd., "ELM-100" manufactured by Sumitomo Chemical Co., Ltd., etc. These may be used alone or in combination of two or more types.

[0028] The epoxy equivalent of the liquid epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. When it is in this range, the crosslink density of the cured product is sufficient, and an insulating layer with small surface roughness can be obtained. The epoxy equivalent can be measured according to JIS K7236, and is the mass of a resin containing one equivalent of epoxy groups.

[0029] The weight average molecular weight of the liquid epoxy resin is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0030] From the viewpoint of obtaining a resin composition having a low melt viscosity, the viscosity of the (A) liquid epoxy resin at 25°C is preferably 300 mPa·s or more, more preferably 500 mPa·s or more, even more preferably 1000 mPa·s or more, and is preferably 5000 mPa·s or less, more preferably 4000 mPa·s or less, even more preferably 3000 mPa·s or less. The viscosity can be measured, for example, using an E-type viscometer.

[0031] The content of the (A) liquid epoxy resin is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining a resin composition having a low melt viscosity. The upper limit of the content of the epoxy resin is preferably 20% by mass or less, more preferably 15% by mass or less, and particularly preferably 10% by mass or less, from the viewpoint of significantly obtaining the desired effects of the present invention.

[0032] In the present invention, unless otherwise specified, the content of each component in the resin composition is a value when the non-volatile components in the resin composition are taken as 100 mass%, and the non-volatile components mean all non-volatile components in the resin composition excluding the solvent.

[0033] From the viewpoint of obtaining a resin composition having a low melt viscosity, the content of the liquid epoxy resin (A) is preferably 2% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, when the total content of the components (A) to (D) is taken as 100% by mass. From the viewpoint of obtaining the desired effects of the present invention significantly, the upper limit of the content of the liquid epoxy resin (A) is preferably 12% by mass or less, more preferably 10% by mass or less, and particularly preferably 9% by mass or less.

[0034] <(B) Solid epoxy resin with an epoxy equivalent of 200 g / eq. or more> The resin composition contains, as component (B), a solid epoxy resin (B) having an epoxy equivalent of 200 g / eq. or more. The solid epoxy resin (B) having an epoxy equivalent of 200 g / eq. or more as component (B) does not include those corresponding to the above-mentioned component (A). By including the solid epoxy resin (B) in the resin composition, it is possible to lower the minimum melt viscosity of the resin composition and also to increase the glass transition temperature of the cured product of the resin composition. The solid epoxy resin (B) having an epoxy equivalent of 200 g / eq. or more may be used alone or in combination of two or more.

[0035] From the viewpoint of obtaining the effect of the present invention remarkably, the (B) component preferably contains a solid epoxy resin having three or more epoxy groups in one molecule, and more preferably contains a solid epoxy resin having three functionalities. The (B) component preferably has an aromatic structure, and when two or more (B) components are used, it is more preferable that at least one of them has an aromatic structure. The ratio of the (B) component having three or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more, based on 100% by mass of the non-volatile components of the (B) component. As an embodiment of the (B) component, the (B) component is preferably a solid epoxy resin having a trifunctional or more aromatic structure, and more preferably a solid epoxy resin having a trifunctional aromatic structure.

[0036] The component (B) preferably contains a resin represented by formula (B-1). [ka] In the formula, R 1 , R 2 , and R 3 each independently represents an alkylene group which may have a substituent, an oxygen atom, or an oxyalkylene group which may have a substituent; R 4 represents an alkyl group which may have a substituent, or a hydrogen atom; R 5 represents an alkylene group which may have a substituent.

[0037] R 1 , R 2 , and R 3 each independently represents an alkylene group which may have a substituent, an oxygen atom, or an oxyalkylene group which may have a substituent.

[0038] The alkylene group which may have a substituent may be linear, branched, or cyclic, and is preferably a linear or branched hydrocarbon group, more preferably a linear one. The alkylene group is preferably an alkylene group having 1 to 10 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, and even more preferably an alkylene group having 1 to 3 carbon atoms. The number of carbon atoms does not include the number of carbon atoms of the substituent. Examples of the alkylene group include a methylene group, a 1,1-dimethylmethylene group, an ethylene group, a propylene group, an n-butylene group, an s-butylene group, a t-butylene group, a pentylene group, a hexylene group, a heptylene group, an octylene group, a nonylene group, and a decylene group, and among these, a methylene group, an ethylene group, and a propylene group are preferred, and a methylene group is more preferred.

[0039] The oxyalkylene group which may have a substituent may be linear, branched, or cyclic, and is preferably a linear or branched hydrocarbon group, more preferably a linear one. The oxyalkylene group is preferably an oxyalkylene group having 1 to 10 carbon atoms, more preferably an oxyalkylene group having 1 to 6 carbon atoms, and even more preferably an oxyalkylene group having 1 to 3 carbon atoms. The number of carbon atoms does not include the number of carbon atoms of the substituent. Examples of the oxyalkylene group include an oxymethylene group, an oxyethylene group, an oxypropylene group, an oxyn-butylene group, an oxys-butylene group, an oxyt-butylene group, an oxypentylene group, an oxyhexylene group, an oxyheptylene group, an oxyoctylene group, an oxynonylene group, and an oxydecylene group, and among these, an oxymethylene group, an oxyethylene group, and an oxypropylene group are preferred, and an oxymethylene group is more preferred.

[0040] R 1 , R 2 , and R 3 From the viewpoint of achieving remarkable effects of the present invention, each of the groups preferably independently represents an oxyalkylene group which may have a substituent, and more preferably represents an oxymethylene group.

[0041] R 4 represents an alkyl group which may have a substituent, or a hydrogen atom. The alkyl group which may have a substituent may be linear, branched, or cyclic. The alkyl group is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 5 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, and particularly preferably an alkyl group having 1 or 2 carbon atoms. The number of carbon atoms does not include the number of carbon atoms of the substituent. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a sec-butyl group, an isobutyl group, a tert-butyl group, and a pentyl group, and the like are preferable, with a methyl group and an ethyl group being more preferable.

[0042] R 4From the viewpoint of achieving remarkable effects of the present invention, it is preferable for R to represent an alkyl group which may have a substituent, and it is more preferable for R to represent a methyl group.

[0043] R 5 represents an alkylene group which may have a substituent, R 1 R is the same as the alkylene group which may have a substituent represented by R 5 From the viewpoint of obtaining the effects of the present invention remarkably, preferably represents a methylene group or a 1,1-dimethylmethylene group, and more preferably represents a 1,1-dimethylmethylene group.

[0044] R 1 , R 2 , and R 3 An alkylene group, an oxyalkylene group, R 4 The alkyl group represented by R 5 The alkylene group represented by may have a substituent. Examples of the substituent include a halogen atom, an alkyl group, an alkoxy group, an aryl group, an arylalkyl group, a silyl group, an acyl group, an acyloxy group, a carboxy group, a sulfo group, a cyano group, a nitro group, a hydroxy group, a mercapto group, and an oxo group.

[0045] Examples of the resin represented by formula (B-1) include, but are not limited to, the following resins. [ka]

[0046] Component (B) may be a commercially available product, such as "VG3101L" manufactured by Air Water Inc., "1031S" manufactured by Mitsubishi Chemical Corporation, "ZX-1542" manufactured by Nippon Steel Chemical Co., Ltd., "EX-321" manufactured by Nagase ChemteX Corporation, "NC7000L" and "YL7890" manufactured by Nippon Kayaku Co., Ltd., "YL7800" and "jER1010" manufactured by Mitsubishi Chemical Corporation, etc.

[0047] The epoxy equivalent of the (B) component is 200 g / eq. or more, preferably 205 g / eq. or more, more preferably 208 g / eq. or more, from the viewpoint of obtaining a resin composition having a high glass transition temperature and a low minimum melt viscosity. There is no particular upper limit, but it is preferably 5000 g / eq. or less, more preferably 3000 g / eq. or less, even more preferably 2000 g / eq. or less, 1000 g / eq. or less, or 500 g / eq. or less. The epoxy equivalent can be measured according to JIS K7236 and is the mass of a resin containing one equivalent of epoxy groups.

[0048] The weight average molecular weight of the component (B) is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0049] The content of the (B) component is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass, from the viewpoint of obtaining a cured product with a high glass transition temperature and a resin composition with a low melt viscosity. The upper limit of the epoxy resin content is preferably 40% by mass or less, more preferably 35% by mass or less, particularly preferably 30% by mass or less, 20% by mass or less, or 15% by mass or less, from the viewpoint of significantly obtaining the desired effects of the present invention.

[0050] From the viewpoint of obtaining a cured product with a high glass transition temperature and a resin composition with a low melt viscosity, the content of the (B) component, relative to the total content of the (A) to (D) components being 100 mass%, is preferably 15 mass% or more, more preferably 25 mass% or more, even more preferably 35 mass% or more or 40 mass% or more, and is preferably 55 mass% or less, more preferably 50 mass% or less, and particularly preferably 45 mass% or less.

[0051] When the content of the (B) component when the nonvolatile components in the resin composition are taken as 100% by mass is b and the content of the (A) component when the nonvolatile components in the resin composition are taken as 100% by mass is a, from the viewpoint of significantly obtaining the effects of the present invention, a / b is preferably 0.05 or more, more preferably 0.1 or more, even more preferably 0.15 or more, and is preferably 0.5 or less, more preferably 0.3 or less, even more preferably 0.2 or less.

[0052] <(C) Maleimide compound> The resin composition contains a maleimide compound (C) as the component (C). The maleimide compound (C) as the component (C) does not include those corresponding to the above-mentioned components (A) and (B). By including the maleimide compound (C) in the resin composition, it is possible to increase the glass transition temperature of the cured product of the resin composition. As described above, when the liquid epoxy resin and the maleimide compound are only included in combination, the dielectric constant of the cured product of the resin composition tends to be high. In the present invention, by including the components (B) and (D) in combination in addition to the liquid epoxy resin and the maleimide compound, it is possible to provide a resin composition with a low melt viscosity that can obtain a cured product with a high glass transition temperature and a low dielectric constant. The maleimide compound (C) may be used alone or in combination of two or more.

[0053] As the (C) maleimide compound, a compound having a 2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl group (so-called maleimide group) can be used. The (C) maleimide compound may be in any of a liquid, semi-solid, and solid form, but is preferably in a solid form from the viewpoint of obtaining the effects of the present invention significantly. The liquid, semi-solid, and solid forms are as described above.

[0054] From the viewpoint of obtaining a cured product having a high glass transition temperature, the number of maleimide groups per molecule of the (C) maleimide compound is 1 or more, preferably 2 or more, more preferably 3 or more, and although there is no upper limit, is preferably 10 or less, more preferably 6 or less, and even more preferably 4 or less. Among these, the (C) maleimide compound is preferably a tri- or higher functional maleimide compound having 3 or more maleimide groups.

[0055] The (C) maleimide compound may be an aliphatic maleimide compound containing an aliphatic amine skeleton, or an aromatic maleimide compound containing an aromatic amine skeleton. Of these, the (C) component is preferably an aromatic maleimide compound containing an aromatic amine skeleton, from the viewpoint of significantly obtaining the effects of the present invention.

[0056] As the (C) maleimide compound, a compound represented by the following formula (C-1) is preferable. [ka] In the formula, X 1 and X 2 each independently represents a single bond or a divalent linking group having 1 to 100 (preferably 1 to 50, more preferably 1 to 20) skeletal atoms selected from carbon atoms, oxygen atoms, sulfur atoms and nitrogen atoms; s represents an integer of 1 or more; 1 , C 2 and C 3 are each independently optionally further substituted with 1 to 3 substituents selected from a halogen atom, an optionally substituted alkyl group, an optionally substituted alkenyl group, an optionally substituted alkoxy group, and an optionally substituted aryl group.

[0057] Examples of the halogen atom include a fluorine atom, a chlorine atom, and a bromine atom.

[0058] The alkyl group which may have a substituent may be any of linear, branched, and cyclic. The alkyl group which may have a substituent is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms. The number of carbon atoms does not include the number of carbon atoms of the substituent. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a cyclopentyl group, and a cyclohexyl group.

[0059] The alkoxy group, which may have a substituent, may be linear, branched, or cyclic. The alkoxy group is preferably an alkoxy group having 1 to 6 carbon atoms, more preferably an alkoxy group having 1 to 3 carbon atoms. The number of carbon atoms does not include the number of carbon atoms of the substituent. Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a sec-butoxy group, a tert-butoxy group, and a pentyloxy group.

[0060] The alkenyl group which may have a substituent may be linear, branched, or cyclic. The alkenyl group is preferably an alkenyl group having 2 to 6 carbon atoms, more preferably an alkenyl group having 2 or 3 carbon atoms. The number of carbon atoms does not include the number of carbon atoms of the substituent. Examples of the alkenyl group include a vinyl group, a 1-propenyl group, a 2-propenyl group, a 2-methyl-1-propenyl group, a 1-butenyl group, a 2-butenyl group, a 3-butenyl group, a 3-methyl-2-butenyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, a 4-pentenyl group, a 4-methyl-3-pentenyl group, a 1-hexenyl group, a 3-hexenyl group, a 5-hexenyl group, and a 2-cyclohexenyl group.

[0061] The aryl group which may have a substituent is preferably an aryl group having 6 to 14 carbon atoms, more preferably an aryl group having 6 to 10 carbon atoms. The number of carbon atoms does not include the number of carbon atoms of the substituent. Examples of the aryl group include a phenyl group, a 1-naphthyl group, and a 2-naphthyl group, and the like, and is preferably a phenyl group.

[0062] C 1 , C 2 and C 3 The alkyl group, alkoxy group, alkenyl group, and aryl group may have a substituent. Examples of the substituent include a halogen atom, an alkyl group, an alkoxy group, an aryl group, an arylalkyl group, a silyl group, an acyl group, an acyloxy group, a carboxy group, a sulfo group, a cyano group, a nitro group, a hydroxy group, a mercapto group, and an oxo group. The number of the substituents is preferably 1 to 3 for each group, and more preferably 1.

[0063] In formula (C-1), the benzene ring C 1 , C 2 and C 3 is preferably not further substituted.

[0064] In formula (C-1), X 1 and X 2 are each independently preferably a divalent linking group having 1 to 100 (preferably 1 to 50, more preferably 1 to 20) skeletal atoms selected from carbon, oxygen, sulfur, and nitrogen atoms, and more preferably a divalent hydrocarbon group having 1 to 20 carbon atoms.

[0065] X 1 and X 2 The divalent linking group in the formula (I) has 1 to 100 (preferably 1 to 50, more preferably 1 to 20) skeletal atoms selected from carbon atoms, oxygen atoms, sulfur atoms, and nitrogen atoms. The "divalent linking group" is preferably -[A'-Ph] a’ -A'-[Ph-A'] b’[wherein A' each independently represents a single bond, -(substituted or unsubstituted alkylene group), -O-, -S-, -CO-, -SO 2 -, -CONH-, -NHCO-, -COO-, or -OCO- (preferably a single bond or -(alkylene group)-), and a' and b' each independently represent an integer of 0 to 2. In this specification, "Ph" represents a 1,4-phenylene group, a 1,3-phenylene group, or a 1,2-phenylene group.

[0066] The alkylene group in the divalent linking group is R 1 The alkylene group may have a substituent. The substituent that the alkylene group may have is as described above, and the number of the substituents is preferably 1 to 3, and more preferably 1.

[0067] X 1 and X 2 The divalent linking group in is specifically, -CH 2 -, -CH 2 CH 2 -, -CH 2 CH 2 CH 2 -, -CH 2 CH 2 CH 2 CH 2 -, -CH 2 CH 2 CH 2 CH 2 CH 2 -, -CH(CH 3 )-, -C(CH 3 ) 2 -, -Ph-, -Ph-Ph-, -CH 2 -Ph-CH 2 -, -CH 2 -Ph-Ph-CH 2 -, -O-, -CO-, -SO 2 -, -NHCO-, -CONH-, -OCO-, -COO-, -O-Ph-O-, -O-Ph-Ph-O-, -O-Ph-SO 2 -Ph-O-, -O-Ph-C(CH 3 )2 -Ph-O-, etc.

[0068] X 1 and X 2 In the above, examples of the divalent hydrocarbon group having 1 to 20 carbon atoms include an alkylene group having 1 to 6 carbon atoms (preferably 1 to 3), an arylene group having 6 to 14 carbon atoms (preferably 6 to 10), or a combination of two or more thereof having 1 to 20 carbon atoms. In the present specification, the term "arylene group" refers to a divalent aromatic hydrocarbon group. Examples of the arylene group include a 1,4-phenylene group, a 1,3-phenylene group, a 1,2-phenylene group, a 1,4-naphthylene group, a 1,5-naphthylene group, a 1,8-naphthylene group, and a 4,4'-biphenylene group.

[0069] X 1 and X 2 Specific examples of the divalent hydrocarbon group having 1 to 20 carbon atoms include -CH 2 -, -CH 2 CH 2 -, -CH 2 CH 2 CH 2 -, -CH 2 CH 2 CH 2 CH 2 -, -CH 2 CH 2 CH 2 CH 2 CH 2 -, -CH(CH 3 )-, -C(CH 3 ) 2 -, -Ph-, -Ph-Ph-, -CH 2 -Ph-CH 2 -, -CH 2 -Ph-Ph-CH 2 --etc.

[0070] In the formula (C-1), s is preferably an integer of 1 to 5, more preferably an integer of 1 to 3, and further preferably 1 or 2.

[0071] Examples of the compound represented by formula (C-1) include the following compounds (C1) to (C2), but are not limited thereto. [ka] (In the formula, s1 represents 1 or 2, and s2 represents 1 or 2.)

[0072] (C) The maleimide compound may be a commercially available product. Examples of commercially available products include "SLK-2600" manufactured by Shin-Etsu Chemical Co., Ltd., "BMI-1500", "BMI-1700", "BMI-3000J", "BMI-689", and "BMI-2500" (dimer diamine structure-containing maleimide compounds) manufactured by Designer Molecules, Inc., "BMI-6100" (aromatic maleimide compound) manufactured by Designer Molecules, "MIR-5000-60T" and "MIR-3000-70MT" (biphenylaralkyl-type maleimide compounds) manufactured by Nippon Kayaku Co., Ltd., "BMI-70" and "BMI-80" manufactured by K.I. Chemical Industry Co., Ltd., and "BMI-2300" and "BMI-TMH" manufactured by Daiwa Kasei Kogyo Co., Ltd. In addition, as the maleimide radical polymerizable compound, a maleimide resin (maleimide compound containing an indane ring skeleton) disclosed in the Japan Institute of Invention and Innovation's Technical Journal Publication No. 2020-500211 may be used.

[0073] From the viewpoint of significantly obtaining the intended effects of the present invention, the maleimide group equivalent of the component (C) is preferably 50 g / eq. to 2000 g / eq., more preferably 100 g / eq. to 1000 g / eq., and even more preferably 150 g / eq. to 500 g / eq. The maleimide group equivalent is the mass of a maleimide compound containing one equivalent of a maleimide group.

[0074] From the viewpoint of obtaining a cured product having a high glass transition temperature, the content of the component (C) is preferably 1 mass % or more, more preferably 1.5 mass % or more, and even more preferably 2 mass % or more, and is preferably 40 mass % or less, more preferably 35 mass % or less, and even more preferably 30 mass % or less, 10 mass % or less, or 5 mass % or less, based on 100 mass % of the non-volatile components in the resin composition.

[0075] From the viewpoint of obtaining a cured product with a high glass transition temperature, the content of component (C), relative to the total content of components (A) to (D) taken as 100 mass%, is preferably 3 mass% or more, more preferably 8 mass% or more, even more preferably 10 mass% or more, and is preferably 20 mass% or less, more preferably 18 mass% or less, even more preferably 15 mass% or less.

[0076] When the content of the (C) component is c when the nonvolatile components in the resin composition are taken as 100% by mass, and the content of the (A) component is a when the nonvolatile components in the resin composition are taken as 100% by mass, from the viewpoint of significantly obtaining the effects of the present invention, a / c is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, and is preferably 1.5 or less, more preferably 1 or less, even more preferably 0.8 or less.

[0077] When the content of the (B) component is b when the nonvolatile components in the resin composition are taken as 100 mass %, from the viewpoint of obtaining a remarkable effect of the present invention, b / c is preferably 1 or more, more preferably 1.5 or more, even more preferably 3 or more, and is preferably 10 or less, more preferably 8 or less, even more preferably 5 or less.

[0078] In addition, from the viewpoint of obtaining the effects of the present invention significantly, (a+b) / c is preferably 1 or more, more preferably 1.5 or more, even more preferably 3 or more, and is preferably 10 or less, more preferably 8 or less, even more preferably 5 or less.

[0079] <(D) Cresol novolac type phenolic resin> The resin composition contains a cresol novolac phenolic resin (D) as the component (D). The cresol novolac phenolic resin (D) as the component (D) does not include those corresponding to the above-mentioned components (A) to (C). The cresol novolac phenolic resin (D) has a function of reacting with the components (A) and (B) to cure the resin composition. In addition, by incorporating the cresol novolac phenolic resin (D) in combination with the maleimide compound (C) in the resin composition, it is possible to increase the glass transition temperature of the cured product of the resin composition and obtain a cured product with a low dielectric constant. The cresol novolac phenolic resin (D) may be used alone or in combination of two or more.

[0080] The number of phenolic hydroxyl groups per molecule of the (D) cresol novolac phenolic resin is, from the viewpoint of obtaining a cured product having a high glass transition temperature and a low dielectric constant, 1 or more, preferably 2 or more, and more preferably 3 or more. There is no upper limit, but the number can be preferably 10 or less, more preferably 6 or less, and even more preferably 4 or less.

[0081] From the viewpoint of obtaining the effects of the present invention more prominently, the (D) cresol novolac phenolic resin is preferably a triazine skeleton-containing cresol novolac phenolic resin having a triazine skeleton.

[0082] (D) The cresol novolac phenolic resin may be a commercially available product, such as "LA3018-50P", "KA-1160", "KA-1163", or "KA-1165" manufactured by DIC Corporation.

[0083] The phenolic hydroxyl group equivalent of the (D) cresol novolac phenolic resin is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The phenolic hydroxyl group equivalent is the mass of the compound per equivalent of the phenolic hydroxyl group.

[0084] The ratio of the amount of the (A) component and the (B) component to all of the (D) components is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.05 to 1:3, and even more preferably 1:0.1 to 1:2, in terms of the ratio of [total number of epoxy groups in the (A) component and the (B) component]:[total number of active groups in the (D) component]. Here, the "total number of epoxy groups in the (A) component and the (B) component" refers to the total value of all values ​​obtained by dividing the mass of the non-volatile components of the (A) component and the (B) component present in the resin composition by the epoxy equivalent. The "total number of active groups in the (D) component" refers to the total value of all values ​​obtained by dividing the mass of the non-volatile components of the (D) component present in the resin composition by the active group equivalent. By setting the ratio of the amount of the (A) component and the (B) component to the (D) component within such a range, the effect of the present invention can be obtained significantly.

[0085] The ratio of the amount of the (A) component to all of the (D) components is preferably in the range of 1:0.01 to 1:1, more preferably 1:0.03 to 1:0.5, and even more preferably 1:0.05 to 1:0.3, in terms of the ratio of [total number of epoxy groups in the (A) component] to [total number of active groups in the (D) component]. Here, the "total number of epoxy groups in the (A) component epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the (A) component present in the resin composition by the epoxy equivalent. By setting the ratio of the (A) component to the (D) component within this range, the effects of the present invention can be obtained significantly.

[0086] The ratio of the amount of the (B) component to all of the (D) components is preferably in the range of 1:0.01 to 1:1, more preferably 1:0.03 to 1:0.5, and even more preferably 1:0.05 to 1:0.3, in terms of the ratio of [total number of epoxy groups in the (B) component] to [total number of active groups in the (D) component]. Here, the "total number of epoxy groups in the epoxy resin of the (B) component" refers to the total value obtained by dividing the mass of the non-volatile components of the (B) component present in the resin composition by the epoxy equivalent. By setting the ratio of the amount of the (B) component to the (D) component within this range, the effects of the present invention can be obtained significantly.

[0087] From the viewpoint of obtaining a cured product having a high glass transition temperature and a low dielectric constant, the content of the (D) component, relative to 100 mass% of the nonvolatile components in the resin composition, is preferably 1 mass% or more, more preferably 3 mass% or more, and more preferably 5 mass% or more, and is preferably 30 mass% or less, more preferably 25 mass% or less, and even more preferably 20 mass% or less, 15 mass% or less, or 10 mass% or less.

[0088] From the viewpoint of prominently obtaining the desired effects of the present invention, the content of component (D) is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, and is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, when the total content of components (A) to (D) is taken as 100% by mass.

[0089] From the viewpoint of obtaining a cured product with a low dielectric constant, the content of the (D) component is preferably greater than the content of the (C) component. Specifically, when the content of the (D) component is d when the nonvolatile components in the resin composition are 100% by mass, and the content of the (C) component is c when the nonvolatile components in the resin composition are 100% by mass, c / d is preferably less than 1, more preferably 0.8 or less, even more preferably 0.5 or less, 0.4 or less, and preferably 0.05 or more, more preferably 0.08 or more, even more preferably 0.1 or more.

[0090] <(E) Inorganic filler> The resin composition may further contain an inorganic filler (E) as an optional component in addition to the above-mentioned components (A) to (D). By including the inorganic filler (E) in the resin composition, it is possible to obtain a cured product having a low linear thermal expansion coefficient.

[0091] (E) An inorganic compound is used as the material of the inorganic filler. (E) Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The (E) inorganic filler may be used alone or in combination of two or more kinds in any ratio.

[0092] Examples of commercially available (E) inorganic fillers include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; "Cellfiers" and "MGH-005" manufactured by Pacific Cement Corporation; and "Sferique" and "BA-1" manufactured by JGC Catalysts and Chemicals Co., Ltd.

[0093] The average particle size of the (E) inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, even more preferably 2 μm or less, and particularly preferably 1.5 μm or less. The lower limit of the average particle size of the (E) inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. The average particle size of the (E) inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is prepared on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0094] The specific surface area of ​​the (E) inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of ​​the (E) inorganic filler is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, and even more preferably 30m 2 / g or less, particularly preferably 10m 2The specific surface area of ​​the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0095] (E) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. Furthermore, the surface treatment agent may be used alone or in any combination of two or more types.

[0096] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0097] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably 0.2% to 3% by mass, and even more preferably 0.3% to 2% by mass.

[0098] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0099] (E) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0100] From the viewpoint of obtaining a cured product with a low linear thermal expansion coefficient, the content of the (E) inorganic filler is 40% by mass or more, preferably 55% by mass or more, and more preferably 60% by mass or more, and is preferably 80% by mass or less, more preferably 78% by mass or less, and even more preferably 75% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0101] <(F) Curing accelerator> The resin composition may further contain a curing accelerator (F) as an optional component in combination with the above-mentioned components (A) to (D). The curing accelerator (F) as the component (F) does not include those corresponding to the above-mentioned components (A) to (E). The curing accelerator (F) functions as a curing catalyst that accelerates the curing of the components (A), (B), and (G) described below.

[0102] As the (F) curing accelerator, a compound that accelerates the curing of the epoxy resin can be used. Examples of such (F) curing accelerators include imidazole-based curing accelerators, phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. Among them, imidazole-based curing accelerators are preferred from the viewpoint of obtaining the effects of the present invention significantly. As the (F) curing accelerator, one type may be used alone, or two or more types may be used in combination.

[0103] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0104] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0105] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0106] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0107] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0108] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0109] From the viewpoint of prominently obtaining the effects of the present invention, the content of the (F) curing accelerator is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.015% by mass or more, and is preferably 0.5% by mass or less, more preferably 0.3% by mass or less, and even more preferably 0.1% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0110] <(G) Semi-solid epoxy resin> The resin composition may further contain a semi-solid epoxy resin (G) as an optional component in combination with the above-mentioned components (A) to (D). The semi-solid epoxy resin (G) as component (G) does not include those corresponding to the above-mentioned components (A) to (F). The semi-solid epoxy resin (G) may be used alone or in combination of two or more kinds.

[0111] Examples of (G) semi-solid epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, and epoxy resins having a butadiene structure, with naphthalene type epoxy resins being more preferred.

[0112] The (G) semi-solid epoxy resin preferably contains a semi-solid epoxy resin having two or more epoxy groups in one molecule. The ratio of the semi-solid epoxy resin having two or more epoxy groups in one molecule to 100% by mass of the non-volatile components of the semi-solid epoxy resin is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0113] As the (G) semi-solid epoxy resin, a semi-solid epoxy resin having two or more epoxy groups in one molecule is preferable, and an aromatic semi-solid epoxy resin having two or more epoxy groups in one molecule is more preferable.

[0114] Specific examples of the (G) semi-solid epoxy resin include "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation. These may be used alone or in combination of two or more kinds.

[0115] The epoxy equivalent of the (G) semi-solid epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 3,000 g / eq., further preferably 80 g / eq. to 2,000 g / eq., and particularly preferably 110 g / eq. to 1,000 g / eq. The epoxy equivalent represents the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0116] The weight average molecular weight (Mw) of the (G) semi-solid epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and further preferably 400 to 1,500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0117] From the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability, the content of the (G) semi-solid epoxy resin is preferably 1% by mass or more, more preferably 3% by mass or more, and particularly preferably 3.5% by mass or more, and is preferably 40% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less, 20% by mass or less, or 15% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0118] <(H) Solid epoxy resin having an epoxy equivalent of less than 200 g / eq.> The resin composition may further contain (H) a solid epoxy resin having an epoxy equivalent of less than 200 g / eq. as an optional component in combination with the above-mentioned (A) to (D) components. The solid epoxy resin (H) having an epoxy equivalent of less than 200 g / eq. as component (H) does not include those corresponding to the above-mentioned (A) to (G) components. The solid epoxy resin (H) having an epoxy equivalent of less than 200 g / eq. may be used alone or in combination of two or more types.

[0119] Examples of the component (H) include tetramethylbisphenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, phenol aralkyl type epoxy resins, phenolphthalimidine type epoxy resins, trisphenylmethane epoxy resins, and the like, with naphthalene type epoxy resins being more preferred.

[0120] The component (H) preferably contains a solid epoxy resin having two or more epoxy groups in one molecule and an epoxy equivalent of less than 200 g / eq., more preferably a solid epoxy resin having three or more epoxy groups in one molecule and an epoxy equivalent of less than 200 g / eq., and even more preferably an aromatic solid epoxy resin having three or more epoxy groups in one molecule and an epoxy equivalent of less than 200 g / eq. The proportion of the solid epoxy resin having two or more epoxy groups in one molecule and an epoxy equivalent of less than 200 g / eq. relative to 100% by mass of the non-volatile components of the solid epoxy resin having an epoxy equivalent of less than 200 g / eq. is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0121] Specific examples of the component (H) include "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "EPPN-502H" (trisphenolmethane-type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "ESN375" (dihydroxynaphthalene novolac-type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK" manufactured by Mitsubishi Chemical Corporation, "YL6121" (biphenyl-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; and "YX8800" (anthracene-type epoxy resin) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more types.

[0122] The epoxy equivalent of component (H) is less than 200 g / eq., preferably 195 g / eq. or less, and more preferably 190 g / eq. or less. There is no particular lower limit, but it is preferably 80 g / eq. or more, more preferably 100 g / eq. or more, and even more preferably 120 g / eq. or more.

[0123] The weight average molecular weight (Mw) of the component (H) is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500.

[0124] From the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability, the content of the (H) component, relative to 100 mass% of the non-volatile components in the resin composition, is preferably 1 mass% or more, more preferably 3 mass% or more, and particularly preferably 3.5 mass% or more, and is preferably 40 mass% or less, more preferably 35 mass% or less, even more preferably 30 mass% or less, 20 mass% or less, or 15 mass% or less.

[0125] <(I) Organic filler> The resin composition may further contain an optional organic filler (I) in combination with the above-mentioned components (A) to (D). The organic filler (I) as component (I) does not include those corresponding to the above-mentioned components (A) to (H). As the organic filler, any organic filler that can be used when forming an insulating layer of a printed wiring board may be used, and examples of the organic filler include rubber particles, polyamide fine particles, silicone particles, etc.

[0126] As the rubber particles, commercially available products may be used, for example, "EXL2655" manufactured by Dow Chemical Japan, "AC3401N" and "AC3816N" manufactured by Aica Kogyo Co., Ltd.

[0127] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (I) organic filler is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, and is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.

[0128] <(J) Other Additives> The resin composition layer may contain (J) other additives as an optional non-volatile component. Examples of (J) other additives include radical polymerizable compounds (excluding those corresponding to component (C)); curing agents (excluding those corresponding to component (D)); thermoplastic resins; elastomers; polymerization initiators; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; triazole-based adhesion imparting agents, tetrazole-based adhesion imparting agents, triazine antioxidants such as hindered phenol-based antioxidants; fluorescent brightening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers; photopolymerization initiation assistants such as tertiary amines; and photosensitizers such as pyrarizones, anthracenes, coumarins, xanthones, and thioxanthones. (J) Other additives may be used alone or in combination of two or more.

[0129] <(K) Solvent> The resin composition may further contain an arbitrary solvent as a volatile component in addition to the non-volatile components described above. As the (K) solvent, a known solvent can be appropriately used, and the type is not particularly limited, and it is preferable that the solvent is an organic solvent. As the (K) solvent, for example, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, anisole, etc.; alcohol-based solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methyl methoxypropionate, etc. Examples of the solvent include ether ester solvents such as ethyl acetate, ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate, ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol), amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone, sulfoxide solvents such as dimethyl sulfoxide, nitrile solvents such as acetonitrile and propionitrile, aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane, and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The (K) solvent may be used alone or in combination of two or more in any ratio.

[0130] From the viewpoint of obtaining the effect of the present invention significantly, the resin composition preferably contains 0.5% by mass or more and 3% by mass or less of the (K) solvent, based on 100% by mass of all the components of the resin composition. Specifically, the (K) solvent is preferably contained in an amount of 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1.5% by mass or less, based on 100% by mass of all the components of the resin composition, and is preferably contained in an amount of 0.5% by mass or more, more preferably 0.8% by mass or more, and even more preferably 1% by mass or more.

[0131] The resin composition can be produced, for example, by mixing the above-mentioned components in any order. In addition, in the process of mixing each component, heating and / or cooling may be performed by appropriately adjusting the temperature. In addition, during or after mixing of each component, stirring may be performed using a stirring device such as a mixer to uniformly disperse each component. Furthermore, if necessary, the resin composition may be subjected to a degassing treatment.

[0132] <Physical properties and applications of resin compositions> The resin composition contains a combination of components (A) to (D), and therefore has a low melt viscosity, which allows a cured product to have a high glass transition temperature (Tg) and a low dielectric constant. In addition, the resin composition can usually also provide a cured product with a low coefficient of linear thermal expansion (CTE).

[0133] The resin composition exhibits a characteristic of low melt viscosity since it contains a combination of components (A) to (D). Therefore, when a cured product is formed from this resin composition, it is possible to obtain a cured product in which the occurrence of warping is suppressed. The melt viscosity of the resin composition is preferably less than 5000 poise, more preferably 5000 poise or less, even more preferably 4900 poise or less, 4000 poise or less, 3000 poise or less, or 2000 poise or less. There is no particular restriction on the lower limit, but it may be preferably 1 poise or more, more preferably 100 poise or more, and even more preferably 200 poise or more. The melt viscosity can be measured by the method described in the examples below.

[0134] The cured product obtained by curing the resin composition at 200°C for 90 minutes exhibits the characteristic of a high glass transition temperature (Tg). Therefore, when an insulating layer is formed from this cured product, an insulating layer with a high glass transition temperature can be obtained. The glass transition temperature of the cured product is preferably 235°C or higher, more preferably 240°C or higher, and even more preferably 245°C or higher or 250°C or higher. The upper limit is not particularly limited, but may be, for example, 500°C or lower. The glass transition temperature can be measured by the method described in the examples below.

[0135] The cured product obtained by curing the resin composition at 200°C for 90 minutes exhibits the characteristic of low dielectric constant. Therefore, when an insulating layer is formed with this cured product, an insulating layer with low dielectric constant can be obtained. The dielectric constant of the cured product is preferably less than 3.7, more preferably 3.7 or less, and even more preferably 3.6 or less. The lower limit is not particularly limited, but may be, for example, 0.0001 or more. The dielectric constant can be measured by the method described in the examples below.

[0136] The cured product obtained by curing the resin composition at 200°C for 90 minutes usually exhibits the characteristic of a low linear thermal expansion coefficient. Therefore, when an insulating layer is formed from this cured product, an insulating layer with a low linear thermal expansion coefficient can be obtained. The linear thermal expansion coefficient of the cured product is preferably less than 22 ppm / °C, more preferably 22 ppm / °C or less, further preferably 20 ppm / °C or less, 15 ppm / °C or less. The lower limit is not particularly limited, but may be, for example, 0.01 ppm / °C or more. The linear thermal expansion coefficient can be measured by the method described in the examples below.

[0137] The resin composition of the present invention is suitable as a resin composition for insulating purposes, and is particularly suitable as a resin composition for forming an insulating layer. Thus, for example, the resin composition is suitable as a resin composition for forming an insulating layer of a printed wiring board (resin composition for forming an insulating layer of a printed wiring board). The resin composition is suitable as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for forming an interlayer insulating layer of a printed wiring board). In addition, the resin composition is suitable as a resin composition for forming an insulating layer for forming a conductor layer (including a rewiring layer) formed on an insulating layer (resin composition for forming an insulating layer for forming a conductor layer). Furthermore, the resin composition is suitable as a resin composition for forming an insulating layer of a rigid substrate (resin composition for forming an insulating layer of a rigid substrate). The resin composition can also be used in a wide range of applications in which the resin composition can be used, such as a resin sheet, a sheet-like laminate material such as a prepreg, a solder resist, an underfill material, a die bonding material, a semiconductor encapsulant, a hole filling resin, a component embedding resin, a multi-chip package, a package-on-package, a wafer-level package, a panel-level package, and a system-in-package.

[0138] [Sheet-type laminated material] The resin composition of the present invention can be used by coating in the form of a varnish, but in general, it is industrially preferable to use the resin composition in the form of a sheet-like laminate material containing the resin composition. As the sheet-like laminate material, the following prepreg and resin sheet are preferred, and the prepreg is more preferred.

[0139] <Prepreg> The prepreg of the present invention comprises a sheet-like fiber base material and the resin composition of the present invention impregnated into the sheet-like fiber base material.

[0140] The sheet-like fiber substrate used for the prepreg is not particularly limited, and any substrate commonly used for prepreg, such as glass cloth, aramid nonwoven fabric, or liquid crystal polymer nonwoven fabric, can be used.

[0141] The diameter yarn density and weft yarn density of the sheet-like fiber substrate are each independently preferably 60 yarns / 25 mm or more, more preferably 70 yarns / 25 mm or more, even more preferably 80 yarns / 25 mm or more, particularly preferably 90 yarns / 25 mm or more, and preferably 120 yarns / 25 mm or less, more preferably 110 yarns / 25 mm or less, and even more preferably 100 yarns / 25 mm or less. When a sheet-like fiber substrate having a diameter yarn density and weft yarn density in such ranges is used, a trench can be smoothly manufactured.

[0142] A specific example of a glass cloth that can be used as the sheet-like fiber substrate is Nitto Boseki's Style WEA1027 (warp density 74 / 25 mm, weft density 74 / 25 mm, fabric mass 19 g / m 2 , thickness 20μm) Asahi Schwebel's "Style 1027MS" (warp density 75 / 25mm, weft density 75 / 25mm, fabric weight 20g / m 2 , thickness 19μm), Asahi Schwebel's "Style 1037MS" (warp density 70 / 25mm, weft density 73 / 25mm, fabric weight 24g / m 2 , thickness 28μm), "1078" manufactured by Arisawa Seisakusho (warp density 54 / 25mm, weft density 54 / 25mm, fabric weight 48g / m 2 , thickness 43μm), "1037NS" manufactured by Arisawa Seisakusho Co., Ltd. (warp density 72 threads / 25mm, weft density 69 threads / 25mm, fabric weight 23g / m 2 , thickness 21μm), "1027NS" manufactured by Arisawa Seisakusho Co., Ltd. (warp density 75 / 25mm, weft density 75 / 25mm, fabric weight 19.5g / m 2 , thickness 16μm), "1015NS" manufactured by Arisawa Seisakusho Co., Ltd. (warp density 95 / 25mm, weft density 95 / 25mm, fabric weight 17.5g / m 2 , thickness 15μm), "1000NS" manufactured by Arisawa Seisakusho Co., Ltd. (warp density 85 / 25mm, weft density 85 / 25mm, fabric weight 11g / m 2 A specific example of a liquid crystal polymer nonwoven fabric is "Veculus" (weight 6 g / m2) made by the melt-blown method of aromatic polyester nonwoven fabric manufactured by Kuraray Co., Ltd. 2 ~15g / m 2) and "Vectran".

[0143] From the viewpoint of thinning the printed wiring board, the thickness of the prepreg is preferably 100 μm or less, more preferably 75 μm or less, even more preferably 55 μm or less, even more preferably 50 μm or less, and is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more.

[0144] The prepreg of the present invention may be laminated with a metal foil as necessary. The metal foil includes one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The metal foil may be a single metal layer or an alloy layer, and the alloy layer may be, for example, a layer formed from an alloy of two or more metals selected from the above group (for example, a nickel-chromium alloy, a copper-nickel alloy and a copper-titanium alloy). Among them, from the viewpoint of versatility of forming the metal foil, cost, ease of patterning, etc., a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred. In addition, the metal foil may be a laminate of a plurality of metal foils.

[0145] In addition, a primer layer may be provided between the prepreg and the metal foil, if necessary, from the viewpoint of forming wiring on the prepreg by a semi-additive method. As the resin composition used for the primer layer, a resin composition that has been conventionally used as a primer layer can be used.

[0146] The prepreg of the present invention can be produced by known methods such as a hot melt method and a solvent method. In the hot melt method, the resin composition is once coated on a release paper having good peelability without being dissolved in an organic solvent, and then laminated onto a sheet-like fiber substrate, or the sheet-like fiber substrate is directly coated with the resin composition by a die coater to produce a prepreg. In the solvent method, the sheet-like fiber substrate is impregnated with the resin composition by immersing the sheet-like fiber substrate in a varnish in which the resin composition is dissolved in an organic solvent, and then dried to produce a prepreg. Furthermore, the prepreg can also be produced by sandwiching the sheet-like fiber substrate between two resin sheets made of the resin composition from both sides and continuously thermally laminating them under heating and pressure conditions. The organic solvent is as described above.

[0147] The prepreg may be produced by a roll-to-roll method or a batch method using a long sheet-like fiber substrate.

[0148] <Resin sheet> The resin sheet of the present invention includes a support and a resin composition layer formed from the resin composition of the present invention provided on the support.

[0149] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more.

[0150] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0151] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0152] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0153] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0154] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0155] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0156] In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.

[0157] The resin sheet can be produced, for example, by preparing a resin varnish by dissolving the resin composition in an organic solvent, applying the resin varnish onto a support using a die coater or the like, and then drying the varnish to form a resin composition layer. The organic solvent is as described above.

[0158] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0159] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0160] [Circuit board and its manufacturing method] The circuit board of the present invention includes a cured layer formed by the cured product of the resin composition of the present invention. The cured product layer can be an insulating layer or a sealing layer. A printed wiring board is a type of circuit board, and the printed wiring board may be a rigid board or a flexible board. The cured product of the resin composition of the present invention has a high glass transition temperature and is suppressed from warping, so that it is suitable for the case where the circuit board is a rigid board.

[0161] The circuit board of the present invention can be produced, for example, by using the above-mentioned prepreg by a method including the following steps (I) and (II). (I) A step of laminating the prepreg on the substrate so that the prepreg is bonded to the substrate. (II) A process of thermally curing the prepreg to form an insulating layer

[0162] In step (I), a substrate is prepared. The substrate may be an inner layer substrate used in a printed wiring board. The substrate is a member that becomes a substrate of a printed wiring board, and examples of the substrate include a glass epoxy substrate, a metal substrate (such as stainless steel or cold-rolled steel sheet (SPCC)), a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a metal layer such as copper foil on the surface as a part of the substrate. For example, a substrate having a peelable first metal layer and a second metal layer on both surfaces may be used. When such a substrate is used, a conductor layer as a wiring layer that can function as a circuit wiring is usually formed on the surface of the second metal layer opposite to the first metal layer. Examples of materials for the metal layer include copper foil, copper foil with a carrier, and materials for the conductor layer described later, and copper foil is preferred. In addition, a commercially available product can be used as the substrate having such a metal layer, and examples thereof include "Micro Thin", an ultra-thin copper foil with a carrier manufactured by Mitsui Mining & Smelting Co., Ltd.

[0163] A conductor layer may be formed on one or both surfaces of the substrate. In the following description, a member including a substrate and a conductor layer formed on the substrate surface may be referred to as a "substrate with wiring layer" as appropriate. Examples of the conductor material included in the conductor layer include materials including one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductor material may be a single metal or an alloy. Examples of the alloy include alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy). Among them, from the viewpoints of versatility, cost, and ease of patterning in the formation of the conductor layer, chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper as single metals; and alloys of nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy as alloys; are preferred. Among these, the single metals chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver and copper; and nickel-chromium alloys; are more preferable, and the single metal copper is particularly preferable.

[0164] The conductor layer may be patterned to function as, for example, a wiring layer. In this case, the line (circuit width) / space (width between circuits) ratio of the conductor layer is not particularly limited, but is preferably 20 / 20 μm or less (i.e., pitch is 40 μm or less), more preferably 10 / 10 μm or less, even more preferably 5 / 5 μm or less, even more preferably 1 / 1 μm or less, and particularly preferably 0.5 / 0.5 μm or less. The pitch does not need to be the same throughout the conductor layer. The minimum pitch of the conductor layer may be, for example, 40 μm or less, 36 μm or less, or 30 μm or less.

[0165] The thickness of the conductor layer depends on the design of the circuit board, but is preferably 3 μm to 35 μm, more preferably 5 μm to 30 μm, further preferably 10 μm to 20 μm, and particularly preferably 15 μm to 20 μm.

[0166] The conductor layer can be formed, for example, by a method including a step of laminating a dry film (photosensitive resist film) on a substrate, a step of forming a pattern by exposing and developing the dry film under predetermined conditions using a photomask to obtain a patterned dry film, a step of forming a conductor layer by a plating method such as electrolytic plating using the developed patterned dry film as a plating mask, and a step of peeling off the patterned dry film. As the dry film, a photosensitive dry film made of a photoresist composition can be used, and for example, a dry film formed of a resin such as a novolac resin or an acrylic resin can be used. The lamination conditions of the substrate and the dry film can be the same as the lamination conditions of the substrate and the prepreg described later. The peeling off of the dry film can be carried out using an alkaline peeling solution such as a sodium hydroxide solution.

[0167] The substrate and the prepreg can be laminated, for example, by hot pressing the prepreg to the substrate. Examples of the member for hot pressing the prepreg to the substrate (hereinafter also referred to as the "hot pressing member") include a heated metal plate (such as a SUS end plate) or a metal roll (such as a SUS roll). It is preferable to press the hot pressing member not directly onto the prepreg, but via an elastic material such as heat-resistant rubber so that the prepreg can sufficiently follow the surface irregularities of the substrate.

[0168] The lamination of the substrate and the prepreg is preferably carried out by a vacuum lamination method. In the vacuum lamination method, the heat-pressure bonding temperature is preferably in the range of 60°C to 160°C, more preferably 80°C to 140°C, the heat-pressure bonding pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably 0.29MPa to 1.47MPa, and the heat-pressure bonding time is preferably in the range of 20 seconds to 400 seconds, more preferably 30 seconds to 300 seconds. The lamination is preferably carried out under reduced pressure conditions of 26.7hPa or less.

[0169] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0170] After lamination, the laminated prepregs may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the prepreg side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0171] In step (II), the prepreg is thermally cured to form an insulating layer. The conditions for thermally curing the prepreg are not particularly limited, and conditions that are usually used for forming an insulating layer of a printed wiring board may be used. The prepreg may be cured by irradiation with active energy rays such as ultraviolet rays, but is usually thermally cured by heating.

[0172] For example, the conditions for thermal curing of the prepreg will vary depending on the type of resin composition, etc., but the curing temperature can be in the range of 120°C to 240°C (preferably in the range of 150°C to 220°C, more preferably in the range of 170°C to 200°C), and the curing time can be in the range of 5 minutes to 120 minutes (preferably in the range of 10 minutes to 100 minutes, more preferably in the range of 15 minutes to 90 minutes).

[0173] Before the prepreg is thermally cured, the prepreg may be preheated at a temperature lower than the curing temperature. For example, the prepreg may be preheated at a temperature of 50° C. or higher and lower than 120° C. (preferably 60° C. or higher and 110° C. or lower, more preferably 70° C. or higher and 100° C. or lower) for 5 minutes or more (preferably 5 to 150 minutes, more preferably 15 to 120 minutes) prior to thermal curing.

[0174] In producing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. If necessary, the steps (I) to (V) of forming the insulating layer and the conductor layer may be repeated to form a multilayer wiring board.

[0175] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0176] Step (IV) is a step of roughening the insulating layer. Usually, smears are also removed in this step (IV). The procedure and conditions of the roughening treatment are not particularly limited. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0177] Examples of the swelling liquid used in the roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0178] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0179] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.

[0180] In one embodiment, the arithmetic mean roughness Ra of the insulating layer surface after the roughening treatment may be preferably 500 nm or less, more preferably less than 200 nm, even more preferably 100 nm or less, and even more preferably less than 100 nm. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0181] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0182] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0183] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0184] The conductor layer is preferably formed by plating. For example, the surface of the insulating layer can be plated by a semi-additive method, a full-additive method, or the like to form a conductor layer having a desired wiring pattern. From the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0185] A plating seed layer is formed on the surface of the insulating layer by electroless plating. Then, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0186] In another embodiment, the printed wiring board of the present invention can be manufactured by using the above-mentioned resin sheet. The manufacturing method of the printed wiring board is the same as that of the case where the prepreg is used.

[0187] [Semiconductor chip package and its manufacturing method] A semiconductor chip package of the present invention includes the above-mentioned circuit board and a semiconductor chip mounted on the circuit board. This semiconductor chip package can be manufactured by bonding the semiconductor chip to the circuit board.

[0188] The bonding conditions between the circuit board and the semiconductor chip such as a silicon chip can be any conditions that allow conductive connection between the terminal electrodes of the semiconductor chip and the circuit wiring of the circuit board. For example, the conditions used in flip-chip mounting of the semiconductor chip can be used. Also, for example, the semiconductor chip and the circuit board may be bonded via an insulating adhesive.

[0189] An example of a bonding method is a method in which a semiconductor chip is pressure-bonded to a circuit board. Pressure-bonding conditions are a pressure-bonding temperature usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and a pressure-bonding time usually in the range of 1 second to 60 seconds (preferably in the range of 5 seconds to 30 seconds).

[0190] Another example of the bonding method is a method of bonding a semiconductor chip to a circuit board by reflow. The reflow conditions may be in the range of 120°C to 300°C.

[0191] After the semiconductor chip is bonded to the circuit board, the semiconductor chip may be filled with a molded underfill material, which may be the above-mentioned resin composition or the above-mentioned resin composition layer of the resin sheet.

[0192] [Semiconductor Devices] A semiconductor device according to an embodiment of the present invention includes the above-mentioned circuit board or semiconductor chip package, and can be manufactured using the above-mentioned circuit board or semiconductor chip package.

[0193] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES

[0194] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Furthermore, the operations described below were performed in an environment of normal temperature and pressure, unless otherwise specified.

[0195] [Example 1] 1) Preparation of resin composition Naphthalene type epoxy resin (DIC "HP-4032SS", epoxy equivalent approx. 145g / eq.) 15 parts, trifunctional epoxy resin (Air Water "VG3101L", epoxy equivalent 210g / eq.) 30 parts, bisphenol type epoxy resin (Nippon Steel Chemical "ZX1059", epoxy equivalent approx. 165g / eq.) 5 parts, naphthalene type epoxy resin (DIC "HP4710", epoxy equivalent approx. 170g / eq.) 16 parts, phenylmethane type maleimide resin (Daiwa Chemical Industry Co., Ltd. "BMI2300") 9 parts, organic filler (Aica Kogyo Co., Ltd. "AC3816N") 3 parts, triazine skeleton and cresol novolac structure A varnish of the resin composition was prepared by uniformly dispersing 50 parts of a phenol-based hardener (DIC Corporation's "LA-3018-50P", phenol equivalent approximately 151 g / eq., 2-methoxypropanol solution with a solid content of 50%), 2 parts of an imidazole-based reaction accelerator (Shikoku Kasei Corporation's "1B2PZ", MEK solution with a solid content of 5 mass%), 30 parts of methyl ethyl ketone (MEK), and 200 parts of an inorganic filler that had been surface-treated with an amino-based silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM573", N-phenyl-3-aminopropyltrimethoxysilane) (amount of surface treatment: 0.6 mass% amino-based silane coupling agent relative to 100 mass% inorganic filler), using a mixer.

[0196] 2) Preparation of prepreg The obtained varnish of the resin composition was applied to a Nitto Boseki Co., Ltd. style WEA1027 (warp density 74 / 25 mm, weft density 74 / 25 mm, fabric mass 19 g / m 2 The resin composition was impregnated into a resin having a thickness of 20 μm and a surface treatment amount of 0.3% by mass, and dried in a vertical drying oven at 105° C. for 5 minutes to prepare a prepreg. The resin composition content in the prepreg was 75% by mass, and the thickness of the prepreg was 50 μm. The length of the prepreg in the vertical direction was 30 cm, and the length in the horizontal direction was 20 cm.

[0197] [Example 2] The organic filler (AC3816N manufactured by Aica Kogyo Co., Ltd.) (3 parts) was not used in Example 1. A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 1 except for the above points.

[0198] [Example 3] In Example 2, 16 parts of the naphthalene type epoxy resin (DIC Corporation's "HP-4710", epoxy equivalent of about 170 g / eq.) was changed to 16 parts of a special multifunctional epoxy resin (Mitsubishi Chemical Corporation's "1031S", epoxy equivalent of about 224 g / eq.). A varnish and a prepreg of the resin composition were obtained in the same manner as in Example 2 except for the above.

[0199] [Example 4] In Example 2, 1) The amount of bisphenol-type epoxy resin (Nippon Steel Chemical's "ZX1059", epoxy equivalent: approx. 165g / eq.) was changed from 5 parts to 20 parts. 2) 15 parts of naphthalene type epoxy resin (DIC Corporation's "HP4032SS", epoxy equivalent: approximately 145 g / eq.) was changed to 16 parts of naphthalene type epoxy resin (DIC Corporation's "HP-4710", epoxy equivalent: approximately 170 g / eq.). A varnish and prepreg of the resin composition were obtained in the same manner as in Example 2, except for the above.

[0200] [Example 5] In Example 1, 200 parts of inorganic filler surface-treated with N-phenyl-3-aminopropyltrimethoxysilane (amount of surface treatment: 0.6% by mass of amino-based silane coupling agent per 100% by mass of inorganic filler) was not used. A varnish and a prepreg of the resin composition were obtained in the same manner as in Example 1 except for the above points.

[0201] [Example 6] In Example 1, the amount of inorganic filler surface-treated with N-phenyl-3-aminopropyltrimethoxysilane (amount of surface treatment: 0.6% by mass of amino-based silane coupling agent per 100% by mass of inorganic filler) was changed from 200 parts to 270 parts. A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 1.

[0202] [Comparative Example 1] In Example 1, 30 parts of a trifunctional epoxy resin (Air Water Corporation's "VG3101L" epoxy equivalent 210 g / eq.) was changed to 30 parts of a trisphenylethane type epoxy resin (Nippon Kayaku Co., Ltd.'s "EPPN-502H" epoxy equivalent 170 g / eq.). A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 1 except for the above.

[0203] [Comparative Example 2] In Example 1, 1) Without using 30 parts of trifunctional epoxy resin (Air Water Corporation's "VG3101L" epoxy equivalent 210g / eq.), 2) The amount of naphthalene-type epoxy resin (DIC "HP4032SS", epoxy equivalent approximately 145 g / eq.) was changed from 15 parts to 45 parts. A varnish and a prepreg of the resin composition were obtained in the same manner as in Example 1 except for the above.

[0204] [Comparative Example 3] 9 parts of the phenylmethane-type maleimide resin ("BMI2300" manufactured by Daiwa Kasei Kogyo Co., Ltd.) was not used in Example 1. A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 1 except for the above points.

[0205] [Comparative Example 4] In Example 1, 1) 50 parts of a phenolic hardener having a triazine skeleton and a cresol novolac structure (DIC Corporation's "LA-3018-50P", phenol equivalent of about 151, 2-methoxypropanol solution with a solid content of 50%) was replaced with 45 parts of a phenolic hardener having a triazine skeleton and a phenol novolac structure (DIC Corporation's "LA-7054-60M", phenol equivalent of about 125 g / eq., methyl ethyl ketone solution with a solid content of 60%). 2) The amount of inorganic filler surface-treated with N-phenyl-3-aminopropyltrimethoxysilane (amount of surface treatment: 0.6% by mass of amino-based silane coupling agent per 100% by mass of inorganic filler) was changed from 200 parts to 190 parts. A varnish and a prepreg of the resin composition were obtained in the same manner as in Example 1 except for the above.

[0206] [Comparative Example 5] In Example 1, 5 parts of the bisphenol type epoxy resin ("ZX1059" manufactured by Nippon Steel Chemical Co., Ltd., epoxy equivalent weight: about 165 g / eq.) was changed to 5 parts of a trisphenylethane type epoxy resin ("EPPN-502H" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent weight: 170 g / eq.). A varnish and a prepreg of the resin composition were obtained in the same manner as in Example 1 except for the above.

[0207] [Comparative Example 6] In Example 5, 30 parts of the trifunctional epoxy resin (Air Water Corporation's "VG3101L" epoxy equivalent 210 g / eq.) was changed to 30 parts of a trisphenylethane type epoxy resin (Nippon Kayaku Co., Ltd.'s "EPPN-502H" epoxy equivalent 170 g / eq.). A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 5 except for the above.

[0208] [Comparative Example 7] In Example 5, 30 parts of the trifunctional epoxy resin (Air Water Corporation's "VG3101L", epoxy equivalent 210 g / eq.) was changed to 45 parts of a naphthalene type epoxy resin (DIC Corporation's "HP4032SS", epoxy equivalent approximately 145 g / eq.). A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 5 except for the above.

[0209] [Comparative Example 8] 9 parts of the phenylmethane-type maleimide resin ("BMI2300" manufactured by Daiwa Kasei Kogyo Co., Ltd.) was not used in Example 5. A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 5 except for the above points.

[0210] [Comparative Example 9] In Example 5, 1) 50 parts of a phenolic hardener having a triazine skeleton and a cresol novolac structure (DIC Corporation's "LA-3018-50P", phenol equivalent of about 151 g / eq., 2-methoxypropanol solution with a solid content of 50%) was replaced with 45 parts of a phenolic hardener having a triazine skeleton and a phenol novolac structure (DIC Corporation's "LA-7054-60M", phenol equivalent of about 125 g / eq., methyl ethyl ketone solution with a solid content of 60%). 2) The amount of naphthalene-type epoxy resin (DIC "HP4710", epoxy equivalent approximately 170 g / eq.) was changed from 16 parts to 8 parts. Except for the above, the same procedure as in Example 5 was repeated to obtain a varnish and a prepreg of the resin composition.

[0211] [Comparative Example 10] In Example 6, 30 parts of the trifunctional epoxy resin (Air Water Corporation's "VG3101L" epoxy equivalent 210 g / eq.) was changed to 30 parts of a trisphenylethane type epoxy resin (Nippon Kayaku Co., Ltd.'s "EPPN-502H" epoxy equivalent 170 g / eq.). A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 6 except for the above.

[0212] [Comparative Example 11] In Example 6, 30 parts of the trifunctional epoxy resin (Air Water Corporation's "VG3101L", epoxy equivalent 210 g / eq.) was changed to 45 parts of a naphthalene type epoxy resin (DIC Corporation's "HP4032SS", epoxy equivalent approximately 145 g / eq.). A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 6 except for the above.

[0213] [Comparative Example 12] 9 parts of the phenylmethane-type maleimide resin ("BMI2300" manufactured by Daiwa Kasei Kogyo Co., Ltd.) was not used in Example 6. A varnish and a prepreg of a resin composition were obtained in the same manner as in Example 6 except for the above points.

[0214] [Comparative Example 13] In Example 6, 1) 50 parts of a phenolic hardener having a triazine skeleton and a cresol novolac structure (DIC Corporation's "LA-3018-50P", phenol equivalent of about 151 g / eq., 2-methoxypropanol solution with a solid content of 50%) was replaced with 45 parts of a phenolic hardener having a triazine skeleton and a phenol novolac structure (DIC Corporation's "LA-7054-60M", phenol equivalent of about 125 g / eq., methyl ethyl ketone solution with a solid content of 60%). 2) The amount of naphthalene-type epoxy resin (DIC "HP4710", epoxy equivalent approximately 170 g / eq.) was changed from 16 parts to 8 parts. Except for the above, the same procedure as in Example 6 was repeated to obtain a varnish and a prepreg of the resin composition.

[0215] <Melt Viscosity Measurement> The prepregs prepared in the examples and comparative examples were cut into pieces with a diameter of 18 mm, and 20 of these were stacked together to obtain a measurement sample. The minimum melt viscosity of the obtained measurement sample was measured using a dynamic viscoelasticity measuring device (UBM's "Rheosol-G3000"). Specifically, the temperature was raised in the range from a starting temperature of 60°C to 200°C, and the dynamic viscoelasticity was measured, and the minimum melt viscosity (poise) was calculated. The measurement conditions were a temperature rise rate of 5°C / min, a measurement temperature interval of 2.5°C, a vibration frequency of 1Hz, and a strain of 1deg. The melt viscosity was evaluated based on the following evaluation criteria. ○: Melt viscosity is less than 5000 poise ×: Melt viscosity is 5000 poise or more

[0216] <Preparation of cured prepreg> The prepregs produced in the Examples and Comparative Examples were laminated on a polyimide film (Toray DuPont "Kapton H", thickness 50 μm) using a vacuum pressure laminator (Meiki Seisakusho "MVLP-500") by vacuum suction at 100°C for 30 seconds and then pressing the prepreg from above with a heat-resistant rubber interposed therebetween at 100°C and a pressure of 0.7 MPa for 30 seconds, and then thermally cured at 200°C for 90 minutes to obtain a cured prepreg.

[0217] <Evaluation of glass transition temperature> The obtained cured product was measured in "tensile mode" using a thermomechanical analyzer (DMA, Seiko Instruments Inc., DMS-6100). The measurement was performed in the range of 25°C to 240°C with a temperature increase rate of 5°C / min. The glass transition temperature (Tg) was evaluated based on the following evaluation criteria. 〇: Glass transition temperature is 235℃ or higher ×: Glass transition temperature is less than 235°C

[0218] <Evaluation of dielectric constant> The obtained cured product was cut into a test piece having a width of 2 mm and a length of 80 mm. The dielectric constant of the test piece was measured by a cavity resonance perturbation method using an Agilent Technologies HP8362B at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C. The measurement was performed on two test pieces, and the average value was calculated. The dielectric constant was evaluated based on the following evaluation criteria. ○: Dielectric constant is less than 3.7 ×: Dielectric constant is 3.7 or more

[0219] <Evaluation of coefficient of linear thermal expansion (CTE)> The obtained cured product was measured in "tensile mode" with a load of 1N using a thermomechanical analyzer (TMA, Hitachi High-Tech Science, TMA / SS7100). The measurement was performed twice, the first time in the range of 25°C to 200°C with a temperature increase of 5°C / min, and the second time in the range of 25°C to 260°C. From the second measurement result, the linear thermal expansion coefficient (ppm / °C) from 30 to 150°C was calculated. The linear thermal expansion coefficient was evaluated based on the following evaluation criteria. 〇: Linear thermal expansion coefficient is less than 22 ppm / ℃ ×: Linear thermal expansion coefficient is 22 ppm / ℃ or more

[0220] [Table 1]

[0221] [Table 2]

[0222]

Table 3

Claims

1. (A) a liquid epoxy resin, (B) a solid epoxy resin having an epoxy equivalent of 200 g / eq. or more and 5000 g / eq. or less; (C) a maleimide compound, and (D) a cresol novolac phenolic resin, A resin composition, wherein the component (B) contains a resin represented by the following formula (B-1): 【Chemistry 1】 In formula (B-1), R 1 , R 2 , and R 3 each independently represent an alkylene group which may have a substituent, an oxygen atom, or an oxyalkylene group which may have a substituent; R 4 represents an alkyl group which may have a substituent, or a hydrogen atom; and R 5 represents an alkylene group which may have a substituent.

2. The resin composition according to claim 1 , wherein the component (B) comprises a trifunctional solid epoxy resin.

3. A resin composition as described in claim 2, wherein the proportion of the trifunctional solid epoxy resin is 50 mass% or more and 100 mass% or less relative to 100 mass% of component (B).

4. The resin composition described in claim 1, wherein the resin represented by formula (B-1) includes a resin represented by the following formula (B-2): 【Chemistry 2】

5. 2. The resin composition according to claim 1, wherein the content of the component (A) is 2% by mass or more and 12% by mass or less, when the total amount of the components (A) to (D) is 100% by mass.

6. 2. The resin composition according to claim 1, wherein the content of the component (B) is 15% by mass or more and 55% by mass or less, when the total amount of the components (A) to (D) is 100% by mass.

7. 2. The resin composition according to claim 1, wherein the content of the component (C) is 3% by mass or more and 20% by mass or less, when the total amount of the components (A) to (D) is 100% by mass.

8. The resin composition according to claim 1, wherein the content of the component (D) is 15% by mass or more and 50% by mass or less, when the total amount of the components (A) to (D) is 100% by mass.

9. The resin composition according to claim 1 , wherein the content of the component (D) is greater than the content of the component (C).

10. The resin composition according to claim 1 , further comprising (E) an inorganic filler.

11. The resin composition according to claim 10, wherein the content of the component (E) is 40% by mass or more and 80% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass.

12. The resin composition according to claim 1 , further comprising (F) a curing accelerator.

13. The resin composition according to claim 12, wherein the component (F) comprises an imidazole-based curing accelerator.

14. The resin composition according to claim 1 , wherein the resin composition contains 0.5% by mass or more and 3% by mass or less of a solvent relative to 100% by mass of all components of the resin composition.

15. A prepreg comprising a sheet-like fiber substrate and the resin composition according to any one of claims 1 to 14 impregnated into the sheet-like fiber substrate.

16. A circuit board comprising a cured layer formed from the cured product of the resin composition according to any one of claims 1 to 14.

17. 17. A semiconductor chip package comprising the circuit board according to claim 16 and a semiconductor chip mounted on the circuit board.

18. A semiconductor device comprising the semiconductor chip package of claim 17.

Citation Information

Patent Citations

  • Resin composition, prepreg, laminate, and printed wiring board

    JP2014185221A

  • Resin composition

    JP2020090570A

  • Molybdenum compound powder, prepreg, and laminate

    WO2013047203A1